25a+4a-36a+3=

Simple and best practice solution for 25a+4a-36a+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25a+4a-36a+3= equation:


Simplifying
25a + 4a + -36a + 3 = 0

Reorder the terms:
3 + 25a + 4a + -36a = 0

Combine like terms: 25a + 4a = 29a
3 + 29a + -36a = 0

Combine like terms: 29a + -36a = -7a
3 + -7a = 0

Solving
3 + -7a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -7a = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -7a = 0 + -3
-7a = 0 + -3

Combine like terms: 0 + -3 = -3
-7a = -3

Divide each side by '-7'.
a = 0.4285714286

Simplifying
a = 0.4285714286

See similar equations:

| 14+42=24 | | 19-43= | | 10/x=6/15 | | 5(x-4)+9.1=19.1 | | 6/6i | | -6d-5d+7d=72 | | 4.22=n+1.8 | | (13x-2y)-(4v+6w)+(12+7x)-(15w+9y)+(3x-16)-(5y+11w)+(2x-8)= | | 2-b=-2(3b-5)-1 | | 6ln(4x+4ln(x))=0 | | 4(x+4)+4-10x=30 | | -3p+3=9 | | 8-5/3x≥9 | | -16x^2+62x+9=17 | | -(x-1)-0.2=3.8 | | 3y+1+2y+2=180 | | 3x-x+8=4(2x+3) | | 3x-(2x+7)=5 | | 12X=8616 | | -3(x-2)=5 | | 4-7d=f-12 | | 7y-4=24-4y | | Y+0.4=0.8 | | (-9.8*x^2)+5*x=0 | | 10x+1=6(2x+1)-25 | | 10+x+2(10+x)=130 | | -5=(p^2)-10p | | 82=-9x-8 | | -2x-3=-4c+3 | | 10+2x+2(10+x)=130 | | -2n+4(3n+8)=4n+7(2n-8) | | 2(3x+1)=4x+2 |

Equations solver categories